2022
DOI: 10.1096/fasebj.2022.36.s1.0r514
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for Antiviral Action of EDP‐235: A Potent and Selective SARS‐CoV‐2 3CLpro Inhibitor for the Treatment of Covid 19

Abstract: To date, there are no approved oral antiviral therapies that can be administered early in the course of COVID‐19 to suppress progression of the disease or for prophylaxis. EDP‐235 is a potent and selective inhibitor of SARS‐CoV‐2 3C‐like protease (3CLpro). EDP‐235 inhibits SARS‐CoV‐2 3CLpro protease activity with an IC50 of 5.8 ± 3.7 nM and retains its activity against variant 3CLpro proteins from multiple SARS‐CoV‐2 lineages (IC50range of 2.8­–5.8 nM). 3CLpro protease activity progress curves showed significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Also of interest, the SARS-CoV-2 M pro inhibitor EDP-235 ( 85 ) from Enanta Pharmaceuticals 319 recently met the primary end point of a phase 2 clinical trial without the coadministration of ritonavir (NCT05616728). In this case, 13 patents from this company claim a very large variety of peptides sometimes featuring conformational locks related to the one depicted above.…”
Section: Inhibitors Of the Sars-cov-2 Main Proteasementioning
confidence: 99%
“…Also of interest, the SARS-CoV-2 M pro inhibitor EDP-235 ( 85 ) from Enanta Pharmaceuticals 319 recently met the primary end point of a phase 2 clinical trial without the coadministration of ritonavir (NCT05616728). In this case, 13 patents from this company claim a very large variety of peptides sometimes featuring conformational locks related to the one depicted above.…”
Section: Inhibitors Of the Sars-cov-2 Main Proteasementioning
confidence: 99%
“…83 Researchers at the German Center for Infection Research (DZIF) at the University of Lübeck have identified RHCDS-13b (structure not disclosed), a "second-generation" derivative derived from an ɑ-keto-amide through studies employing the main protease's crystal structure. 84 EDP-235 from Enanta 85 (structure not disclosed, IC 50 range of 2.8 to 5.8 nM against variant 3CLpro proteins from multiple SARS-CoV-2 lineage), 86 entered a phase I single and multiple ascending dose study to evaluate the safety, tolerability, and pharmacokinetics of EDP-235 in healthy volunteers in February 2022. In March 2022, the U.S. Food and Drug Administration granted Fast Track designation for EDP-235.…”
Section: Inhibiting Viral Replicationmentioning
confidence: 99%
“…2 Both aims have been achieved in record time, the latter initially being driven by investigations into repurposing existing drugs, which has produced relatively few effective treatment options. 3 The search for novel SARS-CoV-2 antivirals, on the other hand, has led to the development of molnupiravir by Merck, 4 EDP-235 by Enanta, 5 S-217622 by Shionogi, 6 and several others. 7 The first such antiviral to receive approval by the FDA, Paxlovid, is an orally-active combination of the SARS-CoV-2 main protease inhibitor nirmatrelvir (1; PF-07321332) and the HIV antiviral ritonavir, disclosed by Pfizer in late 2021.…”
Section: Introductionmentioning
confidence: 99%